LIVESTOCK HEALTH MONITORING SYSTEM USING RADIO FREQUENCY INDENTIFICATION (RFID) - LIEW, CHUNG LIM (Universiti malaysia sarawak (UNIMAS), 2015)
This thesis describes the design and development of livestock health monitoring system by incorporating sensor technology to monitor the temperature of the livestock. Currently, the monitoring process in farming management system is done manually. The system will implement Radio Frequency Identification (RFID) technology to replace the manual task into a computerized system, as RFID is a low cost, effective and efficient solution in monitoring livestock. An RFID tag is attached to the livestock, for example, cows, and this system will enable the farmers to detect if any of their livestock, is unwell by observing their temperature and viewing their health history using a system interface as these information is stored into a local database. This will also assist the farmers to prevent losses due to animals' poor health as Well as to ensure that any sick animals to be identified and separated from the healthy ones to avoid the spread of any diseases in the farm. To date, there is no previous work that includes RFID sensors has been done in this domain.